Implementasi Maslahah Mursalah sebagai Alternatif Hukum Islam dan Solusi Problematika Umat - Abu Yazid Adnan Quthny; Nina Agus Hariati (Fakultas Syariah Institut Ilmu Keislaman Zainul Hasan, 2019)
In the approach of Islamic law, Maslahah mursalah is a proposition to establish a new problem that has not been explicitly mentioned in the main sources, the Qur’an and As-Sunnah, both accepted and rejected. Maslahah mursalah as an option for this legal proposition begins with the Passed away of the Prophet Muhammad SAW. Along with this happened, the revelation of the Qur’an has stopped coming down, and the words of the Prophet have stopped too. Meanwhile, problems continue to develop from time to time along with the development of the community itself. This is where the idea of Maslahah mursalah emerges as an option for the proposition of Islamic law. Please note, in the application, Maslahah mursalah is based on benefit. Looking at the main basis of this argument, understanding and knowing about the theory of benefit becomes a necessity in the use of maslahah as a proposition of Islamic law. Maslahah is a concept that departs from the main purpose of Islamic law, known as maqashid as-sharia. According to Imam As-Syatibi, the main orientation of maqashid as-sharia is to provide protection and protection against five things, namely religion, self, lineage, reason, and wealth. These five aspects are very fundamental things in life, so that damage to one aspect alone will cause extraordinary negative implications. Thus, maslahah is the main consideration in evaluating the value of benefits and harm from a problem that has just emerged in people’s lives. An order to assess benefits and madharat, then weigh which one is greater, the benefits or the madharat (damage). Keywords: Maslahah mursalah, law alternative, Islamic law